Parallel use of a convolutional neural network and bagged tree ensemble for the classification of Holter ECG. (12th September 2018) - Plesinger, Filip; Nejedly, Petr; Viscor, Ivo; Halamek, Josef; Jurak, Pavel
Abstract: The automated detection of arrhythmia in a Holter ECG signal is a challenging task due to its complex clinical content and data quantity. It is also challenging due to the fact that Holter ECG is usually affected by noise. Such noise may be the result of the regular activity of patients using the Holter ECG—partially unplugged electrodes, short-time disconnections due to movement, or disturbances caused by electric devices or infrastructure. Furthermore, regular patient activities such as movement also affect the ECG signals and, in connection with artificial noise, may render the ECG non-readable or may lead to misinterpretation of the ECG. Objective : In accordance with the PhysioNet/CinC Challenge 2017, we propose a method for automated classification of 1-lead Holter ECG recordings. Approach : The proposed method classifies a tested record into one of four classes—'normal', 'atrial fibrillation', 'other arrhythmia' or 'too noisy to classify'. It uses two machine learning methods in parallel. The first—a bagged tree ensemble (BTE)—processes a set of 43 features based on QRS detection and PQRS morphology. The second—a convolutional neural network connected to a shallow neural network (CNN/NN)—uses ECG filtered by nine different filters (8×  envelograms, 1×  band-pass). If the output of CNN/NN reaches a specific level of certainty, its output is used. Otherwise, the BTE output is preferred. Main results : The proposed method was trained using a reduced version of the public PhysioNet/CinC Challenge 2017 dataset (8183 records) and remotely tested on the hidden dataset on PhysioNet servers (3658 records). The method achieved F1 test scores of 0.92, 0.82 and 0.74 for normal recordings, atrial fibrillation and recordings containing other arrhythmias, respectively. The overall F1 score measured on the hidden test-set was 0.83. Significance : This F1 score led to shared rank #2 in the follow-up PhysioNet/CinC Challenge 2017 ranking.